Development Strategy for Downstream Utilization of Sago Potential in Sungai Tohor Village - Sujianto; Hasim As'ari; Adianto; Dedi Kusuma Habibie (JOURNAL OF COMMUNITY SERVICES PUBLIC AFFAIRS, 2022)
Utilization of regional potential is currently not running optimally, the pattern of development and utilization of regional potential is still focused on fulfilling raw materials that have low selling value, for this reason the role of all parties, local government, community members is needed to be able to participate actively with the academic community to make changes local potential development system. The purpose of this service is to find out the Development of Downstream Potential Utilization of Sago in Tebing Tinggi Timur District, Sungai Tohor Village, Kab. Meranti Islands. As well as identifying and developing innovations in utilizing existing potential, and knowing how the development is carried out. This service method uses a qualitative approach, with qualitative data collection techniques through interviews, observation, literature studies and focus group discussions (FGD). The result of this community service activity is the drafting of a community empowerment and development plan concept in exploiting potential opportunities and challenges both arising from within and from outside their environment.